The Peak Absorbance Wavelength of Photosynthetic Pigments Around Other Stars From Spectral Optimization - Lehmer, Owen R.; Catling, David C.; Parenteau, Mary N.; Kiang, Nancy Y.; Hoehler, Tori M. (Frontiers in Astronomy and Space Sciences, 2021)
In the search for life on other planets, the presence of photosynthetic surface vegetation may be detectable from the colors of light it reflects, which on the modern Earth is a steep increase in reflectance between the red and near-infrared wavelengths, a “red edge.” This edge-like signature occurs at wavelengths of peak photon absorbance, which are the result of adaptations of the phototroph to their spectral environment. On planets orbiting different stellar types, red edge analogs may occur at other colors than red. Thus, knowing the wavelengths at which photosynthetic organisms preferentially absorb and reflect photons is necessary to detect red edge analogs on other planets. Using a numerical model that predicts the absorbance spectrum of extant photosynthetic pigments on Earth from Marosvolgyi and van Gorkom (2010), we calculate the absorbance spectrum for pigments on an Earth-like planet around F through late M type stars that are adapted for maximal energy production. In this model, cellular energy production is maximized when pigments are tuned to absorb at the wavelength that maximizes energy input from incident photons while minimizing energy losses due to thermal emission and building cellular photosynthetic apparatus. We find that peak photon absorption for photosynthetic organisms around F type stars tends to be in the blue while for G, K, and early M type stars, red or just beyond is preferred. Around the coolest M type stars, these organisms may preferentially absorb in the near-infrared, possibly past 1 micron. These predictions are consistent with previous, qualitative estimates of pigment absorptance. Our predicted absorbance spectra for photosynthetic surface organisms depend on both the stellar type and planetary atmospheric composition, especially atmospheric water vapor concentrations, which alter the availability of surface photons and thus the predicted pigment absorption. By constraining the absorbance spectra of alien, photosynthetic organisms, future observations may be better equipped to detect the weak spectral signal of red edge analogs.